ANALISIS PEMBANGUNAN BENDUNGAN DIGOEL DI KABUPATEN BOVEN DIGOEL DALAM RANGKA PENGEMBANGAN WILAYAH DI PAPUA - Elieser Numberi; Harmonis Rante; Johni Jonathan Numberi (Jurnal ELIPS (Ekonomi, Lingkungan, Infrastruktur, Pengembangan Wilayah, dan Sosial Budaya), 2022)
One of the pillars of the Food Sovereignty program is the availability of irrigation infrastructure and realizing rice selfsufficiency in Papua Province and Boven Digoel Regency in particular. The concrete effort is to program the development of new water infrastructure with optimum service capacity and the development of potential areas to meet food availability. Merauke River Departement, programmed the Construction of the Digoel Dam in Boven Digoel Regency. This study aims to analyze the development strategy of the Digoel Dam, which includes technical aspects, land use and environment, economic and socio-cultural aspects, benefits and regional development, and asset investment aspects. The method of analysis is quantitative and qualitative. Results study concluded that the technical aspects were carried out through good planning, implementation and supervision of construction. Aspects of land use and the environment, through land use in accordance with the spatial plans of Boven Digoel Regency, development and management that is environmentally sound. Economic and socio-cultural aspects, namely the existence of the Digoel Dam must provide economic benefits to increasing the income and welfare of the community whose social work is farming, raising livestock, fishing and trading. The benefits aspect of the Digoel Dam is as a source of water for irrigation with a potential area of 6,090 Ha, a source of raw water for the surrounding community with a capacity of 32.25 liters/second, a power plant with a planned total electricity generation of 13.96 MW, reducing the potential for flooding in the surrounding area and the potential for flooding in the surrounding area and tourism development to improve the local economy. Aspects of regional development by encouraging the development of the Boven Digoel Region which is supported by sufficient food security. Aspects of asset inventory, namely the existence of the Digoel Dam must provide beneficial benefits from its existence as an economic asset, historical asset and tourism asset.